DESAIN KONSEPTUAL BOTTLE CAPPING MACHINE DENGAN METODE ANTHROPOMETRI - Antoni Yohanes; Firman Ardiansyah Ekoanindiyo (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2023)
Bottle capping or installing milk bottle caps on CV. Memory Susu Nusantara in Semarang city is still done manually by turning the bottle cap by hand. There are many weaknesses in working manually that cause workers to get tired quickly and even blisters, especially on the fingers and wrists. This design or design is planned to use anthropometric data with a sample of 30 employees and the surrounding community as a measure. The measurements used are forward hand reach (JTD) and hand grip (GT). The optimal percentile that will be used is 50. The reach of the hand will be tested for the adequacy and uniformity of the data. Research in the form of this design will later be developed in the form of implementing tools from the designs that have been researched. It can be concluded that later with the Bottle capping tool, workers will be more comfortable at work, besides that it is more effective than the previous manual method. Product design in addition to paying attention to ergonomic size must also pay attention in terms of strength and safety when used.